2020
DOI: 10.1002/jdd.12050
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teachers’ motivation to teach: A multisite study on the associations with the work climate, students’ motivation, and teaching approaches

Abstract: Purpose Using Self‐determination Theory, the purpose was to determine whether work climate, students’ motivation, and teachers’ basic psychological needs could predict clinical teachers’ autonomous and controlled motivation to teach and whether clinical teachers’ motivations could predict student‐ and teacher‐centered teaching approaches Methods A correlational cross‐sectional study was conducted in 2018 across 3 Dental Schools in Chile, in which 206 clinical teachers participated (80.4% response rate). Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…The most important contextual factor associated with teachers feeling more autonomous, competent, and related in their teaching tasks is recognition for the teacher role. This corresponds with literature showing how teacher motivation is supported by policy initiatives, organizational vision and support regarding teaching, the presence of role models, and motivated students (Bartle & Thistlethwaite, 2014 ; Browne et al, 2018 ; Dybowski & Harendza, 2014 ; Engbers et al, 2015 ; Orsini et al, 2020 ; Seabrook, 2003 ; Berg et al, 2013 ; Berg et al, 2015 ). Recognition for teaching can encourage healthcare professionals to take on teaching tasks and boost their motivation for teaching, which is especially important in the often research-focused environment of UH as well as in efficiency-driven contexts with high patient loads such as DTH and PC (Bartle & Thistlethwaite, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most important contextual factor associated with teachers feeling more autonomous, competent, and related in their teaching tasks is recognition for the teacher role. This corresponds with literature showing how teacher motivation is supported by policy initiatives, organizational vision and support regarding teaching, the presence of role models, and motivated students (Bartle & Thistlethwaite, 2014 ; Browne et al, 2018 ; Dybowski & Harendza, 2014 ; Engbers et al, 2015 ; Orsini et al, 2020 ; Seabrook, 2003 ; Berg et al, 2013 ; Berg et al, 2015 ). Recognition for teaching can encourage healthcare professionals to take on teaching tasks and boost their motivation for teaching, which is especially important in the often research-focused environment of UH as well as in efficiency-driven contexts with high patient loads such as DTH and PC (Bartle & Thistlethwaite, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
“…Teacher motivation is a valid measure to assess teacher quality as it is related to beneficial outcomes such as better teacher performance and well-being, and better student learning outcomes, motivation, and well-being (Bakker, 2005 ; Orsini et al, 2020 ; Pelletier et al, 2002 ; Roth et al, 2007 ). Although studies describe different contextual factors associated with teacher motivation, most do not show how exactly these factors relate to motivation, and consequently not how they can be used to enhance teacher motivation (Bartle & Thistlethwaite, 2014 ; Browne et al, 2018 ; Cochran Ward et al, 2013 ; Dahlstrom et al, 2005 ; DaRosa et al, 2011 ; Dybowski & Harendza, 2014 ; Engbers et al, 2015 ; Berg et al, 2013 ; J. W. van den Berg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to SDT, whether working remotely or not, educators' autonomous motivation depends on how they perceive the work environment as supportive of their basic psychological needs of autonomy (feeling that one has choices and concurs with work tasks), competence (feeling a sense of self-efficacy in their role), and relatedness (feeling a sense of connectedness or belonging with important others) (Ten Cate et al 2011). Previous research has shown that when team leaders are more needs-supportive, educators internalise the value of their work efforts and are more autonomously motivated, thus improving performance and displaying higher wellbeing and work satisfaction (Gagné et al 2018, Orsini et al 2020. In light of this, we believe that it is timely and pertinent to raise awareness of how team leaders might support these needs when educators are working in remote environments.…”
Section: Orsini Et Al 2020)mentioning
confidence: 92%
“…We do however need to consider that this might also represent a new way of working for them, where well-intentioned actions might affect and undermine their team's motivation. Previous research has reported team leaders' support as a significant predictor of healthcare educators' optimal motivation to work (Orsini et al 2020).…”
Section: Supporting Motivation In Teams Working Remotely: the Role Of Basic Psychological Needsmentioning
confidence: 97%
“…There are validated instruments for both workers in general [ 8 ] and specific areas of work, such as professors of dentistry [ 9 ], midwives [ 10 ], or high school workers [ 11 ], yet few instruments have been designed for health services or, more specifically, hospital emergency services. In addition, the elements that comprise work climate vary greatly in each field.…”
Section: Introductionmentioning
confidence: 99%